Process Innovation - Heath May (Oz, 2016)
If the late twentieth-century architectural canon was defined by its portrayal as a solo act, the early twenty-first is on a trajectory to usurp this representation. The processes by which architectural works are created are becoming increasingly innovative and diverse, reaching beyond the boundaries of the profession, eschewing the traditional client-practitioner-consultant team structure to include interdisciplinary researchers and academic specialists.